Diffuse indoor optical wireless local area networks - Wong, Damon Wing Kee (2010)
Optical wireless is a form of wireless technology that employs the use of optical waves instead of radio frequency waves as the physical medium for the wireless network. Although radio frequency technology is extremely popular, the achievable bandwidth is limited by regulation which comes about as a result of the interference of various systems occupying the same radio frequency bandwidth. Furthermore, radio frequency systems are inherently susceptible to interception and unauthorized violation due to the penetrative nature of the RF waves. In contrast, optical wireless provides an extremely rich potential in terms of bandwidth, from the hundreds of megahertz to gigahertz and above due to the unregulated optical domain. Furthermore, the confined nature of the optical channel to the physical constraints of the environment would ensure that there is no unnecessary leakage of the optical medium to unauthorized users.